Dampak Implementasi Kebijakan Face-Off Jalan Hos Cokroaminoto terhadap Interaksi Ruang Terbuka Publik - Wafa, Novelian Ahmad Itmamul (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
This study is to determine the impact of the implementation of the Cokroaminoto HOS Road face-off policy on the interaction of public open spaces. This research chose to use a Qualitative Approach with Descriptive Methods. The research location is HOS Cokroaminoto road, data collection was carried out by conducting interview techniques and also documentation studies. In this study, the data validity testing technique used was the triangulation technique. The results in this study are that the use of public open space is divided into three, namely by the public in general, by the community and the government itself. Utilization by the community is used for economic activities, namely for economic activities by sellers in the public open space environment such as street vendors, as well as other economic sectors. Apart from that social activities, such as recreation, entertainment, gathering with family, socializing, resting, and playing.